Eco-Friendly Extraction of Phlorotannins from Padina pavonica: Identification Related to Purification Methods Towards Innovative Cosmetic Applications - Moustapha Nour; Valérie Stiger-Pouvreau; Alain Guenneguez; Laurence Meslet-Cladière; Stéphane Cérantola; Ahmed Ali; Gaelle Simon; Abdourahman Daher; Sylvain Petek (Marine Drugs)
This study focuses on developing innovative and eco-friendly purification methods for the isolation of bioactive compounds derived from Padina pavonica, a brown abundant macroalga in Djibouti. Three distinct fractions, obtained via liquid-liquid extraction (LLE_FAE), solid-phase extraction (SPE_WE50), and flash chromatography (FC_EtOH20), were selected based on their high phenolic content and antioxidant activities. All fractions were also evaluated for their anti-ageing potential by assessing their ability to inhibit two vital skin-ageing enzymes, tyrosinase and elastase. Structural analysis by 1H-13C HMBC NMR and LC-MS revealed a selectivity of phlorotannins depending on the purification methods. The LLE_FAE fraction exhibited greater structural complexity, including compounds such as phloroglucinol, diphlorethol/difucol, fucophlorethol and bifuhalol, which likely contribute to its enhanced bioactivity compared to the fractions obtained by FC_EtOH20 and SPE_WE50, which were also active and enriched only in phloroglucinol and fucophlorethol. These findings highlight the impact of purification techniques on the selective enrichment of specific bioactive compounds and demonstrated the interest of FC or SPE in producing active phlorotannin-enriched fractions. These two purification methods hold strong potential for innovative cosmeceutical applications. Results are discussed regarding the use of P. pavonica as a promising marine resource in Djibouti to be used for the development of cosmetic industry.